1983
DOI: 10.1002/ajmg.1320160207
|View full text |Cite
|
Sign up to set email alerts
|

Hematological abnormalities in newborn infants with down syndrome

Abstract: The hematological status of 81 infants with Down syndrome was reviewed retrospectively. Twenty babies had no hematological evaluation, 33 had a normal hematological status, and 28 had at least one abnormality, either of hematocrit, white cell count, or platelet count. Among these were 18 babies with increased hematocrit, one with decreased hematocrit, four with decreased platelet count, one with increased white cell count, three with increased hematocrit and decreased platelet count, and one with increased pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 9 publications
2
36
0
1
Order By: Relevance
“…[1][2][3] Blood samples were principally collected at birth from umbilical cord blood (on day 0) on days 2 and 5 (screening period for inherited metabolic disorders) and, in addition, on periods of follow-up when patients showed complete blood count abnormalities. Blood samples were immediately centrifuged and stored at À30 1C until assay for TPO levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Blood samples were principally collected at birth from umbilical cord blood (on day 0) on days 2 and 5 (screening period for inherited metabolic disorders) and, in addition, on periods of follow-up when patients showed complete blood count abnormalities. Blood samples were immediately centrifuged and stored at À30 1C until assay for TPO levels.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] These include neutrophilia, thrombocytopenia, polycythemia, transient myeloproliferative disorder (TMD), neutropenia, thrombocytosis, and anemia. [1][2][3] A recent large case series study indicated thrombocytopenia below 150 Â 10 9 per liter in approximately two-third of DS infants during the first week of life, making thrombocytopenia as one of the most common hematological abnormalities. 3 Thrombopoietin (TPO), the ligand for the c-mpl receptor, is the primary regulator of thrombopoiesis and megakaryopoiesis in fetuses and neonates as well as adults.…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell suspensions of bone marrow and spleen cells were prepared and red cells lysed in ACK lysis buffer (150mM NH 4 Cl, 1mM KHCO 3 , 1M ethylenediaminetetraacetic acid). Cells were stained according to standard flow cytometric procedures using the following antibodies: biotinylated anti-Ter119 followed by streptavidin-peridinin-chlorophyll-protein complex, anti-CD19-allophycocyanin, and anti-CD3⑀-phycoerythrin (BD Pharmingen).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Policitemia (MILLER & COSGRIFF, 1983), macrocitose em 65% dos casos por deficiências vitamínicas principalmente relacionada aos folatos e anemias hemolíticas (LUBIN et al, 1992), aumento da concentração intraeritrocitária da superoxidesmutase cobre-zinco (SOD1) (PANTELAKIS et al, 1970), havendo relação desta enzima com a doença de Alzheimer (ANNERÉN et al, 1986;PERCY et al, 1990). …”
Section: 5-aspectos Específicos Na Conduta Da Síndrome De Downunclassified